2017
DOI: 10.1371/journal.pone.0180100
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the way of reporting alpha-Amylase values in saliva in different naturalistic situations: A pilot study

Abstract: The objective of this pilot study was to compare the different ways of measuring salivary alpha-amylase (sAA, enzymatic vs. concentration) and to evaluate the influence that the different ways of reporting the results can have in sAA interpretation. For this purpose, sAA was measured by direct quantification and also by an enzymatic assay in three different naturalistic situations, a physical stressor (situation 1) and two mental stressors of different intensity (situations 2 and 3). The results were expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 33 publications
6
33
0
1
Order By: Relevance
“…Since components present in saliva have different origins, i.e., are locally secreted by salivary glands or oral mucosa, or pass from blood among other, and can be affected by non-uniform salivary flow rate, the need to correct values of salivary biomarker by flow rate, total protein content or salivary osmolarity versus use of their absolute value is being increasingly acknowledged and studied by different authors [25,28]. In this study we aimed to evaluate the results without any adjustment, and we also corrected salivary flow or total protein content to gain knowledge about the possible effect that these corrections can have in this particular disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since components present in saliva have different origins, i.e., are locally secreted by salivary glands or oral mucosa, or pass from blood among other, and can be affected by non-uniform salivary flow rate, the need to correct values of salivary biomarker by flow rate, total protein content or salivary osmolarity versus use of their absolute value is being increasingly acknowledged and studied by different authors [25,28]. In this study we aimed to evaluate the results without any adjustment, and we also corrected salivary flow or total protein content to gain knowledge about the possible effect that these corrections can have in this particular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Hp levels were measured in saliva using a homemade immunoassay as previously described [24]. Salivary alpha-amylase (sAA) activity was measured using a colorimetric commercial kit (Alpha-Amylase, Beckman Coulter Inc., Fullerton, CA, USA) following the IFCC method as previously reported and validated [25].…”
Section: Biochemical Analysismentioning
confidence: 99%
“…Contreras-Aguilar et al revealed that both activity and concentration of amylase vary depending on the stress situation and the method of determination and interpretation. These differences may result from many factors, such as changes in the salivary flow, the concentration of all salivary proteins, and various stressful situations [ 90 ]. Stress and pain are often interrelated events.…”
Section: Determination Of Enzymesmentioning
confidence: 99%
“…In human medicine, saliva is gaining attention as a possible alternate fluid to blood analysis [2]. In dogs, analytes such as C-reactive protein [3], cortisol [4], alpha-amylase [5], adenosine deaminase [6] or muscle enzymes [7] have been successfully measured in saliva.…”
Section: Introductionmentioning
confidence: 99%